Single phase PQ theory based control of active power filter for power quality enhancement in DG connected microgrid - Gayatri, M T L; M Parimi, Alivelu (International Journal of Engineering and Technology, 2018)
The number of DG systems like Photovoltaic and Wind Energy Systems are now penetrating more into the conventional power system. In microgrids, loads and generators are in the close vicinity. However, due to the unpredictable nature of non-conventional energy resources like wind and solar with varying loads, it is almost impossible to maintain an accurate power balance between the source and load. Furthermore, to compensate reactive power and harmonics of this AC microgrid and also to maintain a reasonable power quality, it is essential to use a state-of-the-art controller like shunt active power filter (Sh. APF). This research work is an effort in the same direction wherein the actual environmental data like solar irradiation and wind profile have been collected with the help of the weather monitoring system in BITS-Pilani Hyderabad Campus and this data has been used in conceiving and designing an AC microgrid of suitable capacity. The loads included in this system are both harmonic and reactive in nature. Finally, a Sh. APF with an appropriate control scheme has been incorporated in the proposed AC microgrid so that impeccable power quality is maintained at the load end, apart from achieving a good power balance.